Anosmia pada COVID-19 - Ishak Samuel; Budi Riyanto Wreksoatmodjo (Cermin Dunia Kedokteran, 2021)
Sejak tanggal 11 Maret 2020, WHO telah mendeklarasikan COVID-19 sebagai pandemi. Gejala COVID-19 yang paling umum adalah demam, malaise, dan batuk kering, namun dapat juga muncul gejala gangguan penghidu atau anosmia. Anosmia pada COVID-19 dapat disebabkan oleh invasi langsung oleh virus melalui epitel hidung dan bulbus olfaktorius pada reseptor ACE2. Anosmia pada COVID-19 ini dapat timbul tiba-tiba atau didahului oleh gejala ringan seperti batuk kering. Tatalaksana anosmia pada COVID-19 masih terus berkembang dan diteliti lebih lanjut. Since March 11, 2020, WHO has declared COVID-19 a pandemic. The most common symptoms of COVID-19 are fever, malaise, and dry cough, but there can also be symptoms of olfactory dysfunctions including anosmia. Anosmia in COVID-19 can be caused by direct viral invasion through the nasal epithelium and olfactory bulb at the ACE2 receptor. Anosmia in COVID-19 can spontaneously appear or preceded by mild symptoms such as dry cough. The management of anosmia in COVID-19 is still developing and needs more in-depth research.